Correlation of spiritual health and depression among young adults in a state university in Southern Philippines - Sitty Aizah Mangotara; Ashley Bangcola (Universitas Airlangga, 2022)
Introduction: Respiratory Much of the study on the link between spirituality and mental health has focused on depression because of its prevalence in the Philippine population, especially among the younger generation. This study assessed the respondents' demographic characteristics, their spiritual health, and their level of depression. Methods: The study employed a descriptive-correlational quantitative research design and non-probability convenience sampling to acquire 200 respondents who are undergraduate students aged 18-25 enrolled in a state university in Southern Philippines. The data were examined using frequency distribution, percentage distribution, and Pearson's correlation coefficients. Results: The data indicated that respondents' average spiritual health score was 55.28, indicating a favorable sense of one's relationship with God. The existential well-being score had a mean of 44.56, indicating a moderate level of life fulfillment and meaning. Furthermore, the total score for all depressed symptoms was 23.32, indicating that people who took part in the survey during the pandemic suffered moderate to severe depression. Correlation analysis found a negative correlation between spiritual health and the level of depression (r=.458, p=0.001). Conclusions: The study concluded that spiritual health, as expressed through existential well-being and spiritual health, is a separate component that lends explanatory power to mental well-being prediction. The study advises heads of health sectors in various institutions to intensify their fight against depression. Additional research is also strongly encouraged.